Electronic Structures and Optical Properties for Nano Particles: Experimental and Theoretical Calculations - Aly, Abeer E. (2022)
The use of copper nanoparticles (Cu NPs) and copper oxide nanoparticles (Cu₂O NPs) has increased dramatically both in the medical and industrial fields. In the present study, we have used various techniques like, dynamic light scattering (DLS) for particle size, zeta potential determination, X-ray diffraction (XRD), transmission electron microscope (TEM) and scanning electron microscope (SEM) for development and characterization of Cu and Cu₂O NPs. We have also performed the ab-initio calculations based on the density functional theory (DFT) where the theoretical results are in well accordance with the experimental reports. The Hubbard correction is included over the generalized gradient approximation (GGA) for a better description of Cu and Cu₂O NPs. The plot of densities of states (DOS) and energy band structures of Cu and Cu₂O nanocrystals predicts the metallic and semiconducting nature of Cu and Cu₂O, respectively. The energy bands and DOS shows strong hybridization of Cu-O and predicts the metallic nature of Cu and semiconducting nature of Cu₂O. The optical absorption results show that both the Cu₂O and Cu samples are absorbing strongly at the minimum energy. The band structure of Cu Nano crystals reveals a metallic nature where the valence band crosses the Fermi energy level at W point. However, an indirect energy band gap can be seen above the EF.